2010
DOI: 10.1016/j.learninstruc.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instruction type and dyadic or individual emulation on the quality of higher-order peer feedback in EFL

Abstract: The effect of instruction type and dyadic or individual emulation on the quality of higher-order peer feedback in EFL van Steendam, E.; Rijlaarsdam, G.C.W.; Sercu, L.; van den Bergh, H. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 41 publications
6
65
1
6
Order By: Relevance
“…Along with question prompts, instructors can provide students with a model of reviewing, which guides student reviewers to focus on micro-and macro-level meaning rather than surface features. Previous studies showed that observing a writing or revision model and emulating the model are much beneficial for novice writers (Couzijn 1999;Van Steendam et al 2010;Zimmerman and Kitsantas 2002). In addition, feedback on review comments may improve the quality of review (Cho and Schunn 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with question prompts, instructors can provide students with a model of reviewing, which guides student reviewers to focus on micro-and macro-level meaning rather than surface features. Previous studies showed that observing a writing or revision model and emulating the model are much beneficial for novice writers (Couzijn 1999;Van Steendam et al 2010;Zimmerman and Kitsantas 2002). In addition, feedback on review comments may improve the quality of review (Cho and Schunn 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems very interesting to analyze the writers' feedback in order to understand how the writers used the peer comments to guide their revisions. In addition, more research is needed to examine factors influencing the quality of peer reviewers' comments (e.g., Tsai and Liang 2009;Van Steendam et al 2010;Yang and Tsai 2010). It is crucial when designing peer review activities to understand conditions under which reviewers generate high-quality comments for peer authors and their own learning.…”
Section: Discussionmentioning
confidence: 99%
“…Research highlights some potential problems inherent in peer response practice and they lie in, Pre -print draft of paper in press for System, 2014 http://dx.doi.org/10.1016/j.system.2014.03.004 4  L2 writers' different attitudes and expectations towards collaboration and pair or group mechanisms (Carson & Nelson 1994  Learners' beliefs about the relative value of teacher and peer feedback (Morra & Romano, 2008;Nelson & Carson, 1998)  L2 learners' inability to detect errors, offer valid feedback, and lack of experience and unfamiliarity with peer evaluation technique (Tsui & Ng, 2000)  Lack of trust in their peers' writing skills and reservations to each other's advice (Rollinson, 2005;Yang et al, 2006) Failure to achieve the goals of peer evaluation is more likely to happen in contexts where learners have had limited formal exposure to writing skills training and have not yet developed adequate evaluative criteria for good writing. Learning to write on the one hand, and to evaluate on the other, is a dual agenda which may eventually lead to cognitive overload and frustration in novice writers (van Steendam et al, 2010). Therefore, teacher intervention, whether direct or indirect, may be needed at all stages of the writing process particularly when dealing with EFL students at lower levels of proficiency.…”
Section: Peer Collaborationmentioning
confidence: 99%
“…The promotion and valuing of peer learning (Slavin 1991) is a common motivation for implementing and studying peer assessment (Topping 2003;Gielen et al 2011;Kollar and Fischer, 2010;van Steendam et al 2010;van Zundert, Sluijsmans and van Merriënboer 2010). Peer assessment is often used to generate and evaluate evidence of typical peer learning activities such as team working, reflective thinking without the guidance of a teacher, and domain specific communication skills (Boud, Cohen and Sampson 1999).…”
Section: Comparative Judgementmentioning
confidence: 99%